Pengembangan Sistem Informasi Ramah Buta Warna Menggunakan Desain Inklusif bagi Mahasiswa Perguruan Tinggi - Erkamim, Moh.; Fitriyad, Farid; Wartono, W; Pamungkas, M Rizal Fernandita (STIKOM Tunas Bangsa Pematangsiantar, 2023)
People with color blindness often experience difficulties when accessing a system and must spend extra effort to distinguish several elements related to color. To help people with color blindness understand information from the visual elements of an information system, especially those provided by universities, research has been carried out to develop an information system framework that can be widely utilized by applying an inclusive design approach. Development of information systems using an inclusive design approach using the SDLC prototyping model and testing people with color blindness using surveys and semi-structured interviews to assess the usability of the information system. Usability measurement uses heuristic evaluation which includes ten aspects, namely visibility of system status, suitability of the system with the real world, user control and freedom, consistency and standards, error prevention, recognition than recall, flexibility and efficiency of use, aesthetics and minimalist design, user identification support, help, and documentation. The results obtained from this study are that the developed information system gets an average percentage score of 86.40% so it is grouped in the